Effectiveness Diabetic Foot Exercises with Video in Reducing Risk of Diabetic Foot Ulcer in Patients with Diabetes Mellitus Type 2 - Ramadhan, Muhamad Alfin; Nuraeni, Ani; Aprianti, Tutty (Universitas Padjadjaran, 2026)
Type 2 diabetes is a chronic metabolic disorder characterized by elevated blood glucose due to impaired glucose uptake or insulin production. This condition can lead to complications, namely diabetic foot ulcers. Handling diabetic foot wounds can be done by doing activities such as foot exercises. This study aims to determine the effectiveness of diabetic foot exercises using video in reducing the risk of foot wounds in patients with type 2 DM. The research method was quasi-experiment with pretest-postest with control group. Sampling using purposive sampling technique. A total of 64 participants were enrolled and divided into an intervention group (n = 32) and a control group (n = 32); the intervention group performed diabetic foot exercises using video guidance for 3 weeks, three times per week, with a duration of 10 minutes per session. Measurements were made with ABI and monofilament test before and after intervention. The data analysis used was the Independent T-Test test. The was that the Monofilament of the right foot and left foot has a P-Value of 0.001 as well as the ABI value data on the right foot has a P-Value of 0.002 and the left foot P-Value of 0.001. Diabetic foot exercises with video media are proven to be effective in reducing the risk of diabetic foot wounds in patients with type 2 diabetes mellitus. For future research, we recommend a longer study duration to allow for a larger sample size and the analysis of additional relevant variables